Rationale, Design and Baseline Characteristics of Participants in the Cardiovascular Outcomes for People Using Anticoagulation Strategies (COMPASS) Trial - Bosch, Jackie; Eikelboom, John W; Connolly, Stuart J; Bruns, Nancy Cook; Lanius, Vivian; Yuan, Fei; Misselwitz, Frank; Chen, Edmond; Diaz, Rafael; Alings, Marco; Lonn, Eva M; Widimsky, Petr; et al. (The Canadian journal of cardiology, 2017)
BACKGROUND: Long-term aspirin prevents vascular events but is only modestly effective. Rivaroxaban alone or in combination with aspirin might be more effective than aspirin alone for vascular prevention in patients with stable coronary artery disease (CAD) or peripheral artery disease (PAD). Rivaroxaban as well as aspirin increase upper gastrointestinal (GI) bleeding and this might be prevented by proton pump inhibitor therapy. METHODS: Cardiovascular Outcomes for People Using Anticoagulation Strategies (COMPASS) is a double-blind superiority trial comparing rivaroxaban 2.5 mg twice daily combined with aspirin 100 mg once daily or rivaroxaban 5 mg twice daily vs aspirin 100 mg once daily for prevention of myocardial infarction, stroke, or cardiovascular death in patients with stable CAD or PAD. Patients not taking a proton pump inhibitor were also randomized, using a partial factorial design, to pantoprazole 40 mg once daily or placebo. The trial was designed to have at least 90% power to detect a 20% reduction in each of the rivaroxaban treatment arms compared with aspirin and to detect a 50% reduction in upper GI complications with pantoprazole compared with placebo. RESULTS: Between February 2013 and May 2016, we recruited 27,395 participants from 602 centres in 33 countries; 17,598 participants were included in the pantoprazole vs placebo comparison. At baseline, the mean age was 68.2 years, 22.0% were female, 90.6% had CAD, and 27.3% had PAD. CONCLUSIONS: COMPASS will provide information on the efficacy and safety of rivaroxaban, alone or in combination with aspirin, in the long-term management of patients with stable CAD or PAD, and on the efficacy and safety of pantoprazole in preventing upper GI complications in patients receiving antithrombotic therapy.
Keywords: směrnice pro lékařskou praxi jako téma; Cardiovascular Diseases; Thrombolytic Therapy; antikoagulancia; trombolytická terapie; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Humans; randomizované kontrolované studie jako téma; Anticoagulants; kardiovaskulární nemoci; lidé